Integrative Organismal Biology: A Journal of the Society for Integrative and Comparative Biology - Integrative Organismal Biology: A Journal of the Society for Integrative and Comparative Biology (Oxford University Press, 2026)
Integrative Organismal Biology: A Journal of the Society for Integrative and Comparative Biology publishes original research, reviews, techniques, methods, best practices, brief communications, opinion pieces, letters and commentaries that span the disciplines of integrative and comparative biology. The journal particularly welcomes contributions that clearly and explicitly encompass concepts from more than one of the topics outlined below, which encompass the full scope of organismal biology including zoology and botany.
FI 0.78
Q2
Keywords: Life Sciences; Ecology & Organismal Biology; Ecología; Biología de los organismos; Acuerdos transformativos; Transformative agreements; Comportamiento animal; Biología del desarrollo evolutivo; Evolución